2021
DOI: 10.1021/acsnano.1c07960
|View full text |Cite
|
Sign up to set email alerts
|

Nanopores in Graphene and Other 2D Materials: A Decade’s Journey toward Sequencing

Abstract: Nanopore techniques offer a low-cost, label-free, and high-throughput platform that could be used in single-molecule biosensing and in particular DNA sequencing. Since 2010, graphene and other two-dimensional (2D) materials have attracted considerable attention as membranes for producing nanopore devices, owing to their subnanometer thickness that can in theory provide the highest possible spatial resolution of detection. Moreover, 2D materials can be electrically conductive, which potentially enables alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 171 publications
0
40
0
Order By: Relevance
“…Porous graphenic nanostructures and other 2D materials have attracted considerable attention for sieving or sensing applications, including potential nucleic-acid sensing and DNA sequencing. It has been theoretically demonstrated that DNA nucleobases inserted into the nanopores of GNRs lead to unique changes in device conductance and allow DNA sequencing . While such biosensing devices have been proven experimentally with top-down preparation of a nanopore GNR with undefined edge structures, measurement sensitivity can be drastically enhanced by using zigzag-edged or topologically insulating GNRs, which are the synthetic challenges to be approached in the future.…”
Section: Synthetic Carbon Materials In the World Of Biologymentioning
confidence: 99%
“…Porous graphenic nanostructures and other 2D materials have attracted considerable attention for sieving or sensing applications, including potential nucleic-acid sensing and DNA sequencing. It has been theoretically demonstrated that DNA nucleobases inserted into the nanopores of GNRs lead to unique changes in device conductance and allow DNA sequencing . While such biosensing devices have been proven experimentally with top-down preparation of a nanopore GNR with undefined edge structures, measurement sensitivity can be drastically enhanced by using zigzag-edged or topologically insulating GNRs, which are the synthetic challenges to be approached in the future.…”
Section: Synthetic Carbon Materials In the World Of Biologymentioning
confidence: 99%
“…We study oxygen transport through few-nanometer-thick Bi x O y Se z and explore further applications by combining the material with monolayer transition-metal dichalcogenides (TMDs). Like many 2D materials�which have made a notable impact across numerous disparate fields, including superconductivity, 16 quantum information science, 17 DNA sequencing, 18 catalysts, 19 transistors, 20 renewable energy, 21 and COVID-19 sensing 22 �monolayer TMDs are quite sensitive to their environment. In the heterostructures we construct, we believe the oxygen transport through the Bi x O y Se z layer allows us to controllably transport oxygen into and out of the interlayer region, thereby reversibly modulating the 2D material's properties with high precision.…”
Section: Introductionmentioning
confidence: 99%
“…Although polymer translocation is a topic that is extensively investigated by polymer physics, some long-standing problems remain unsolved such as the lack of methods to efficiently connect the retention of polymer and the confinement free energy barrier of polymer permeation in the process of nanofiltration at the present level of understanding since related experimental data were reported as early as over half a century . This issue actually slows down further rational design of functional membranes for applications when the concept of a free energy barrier is relevant such as the sensing of single biological polymers, as well as the process of water purification and separation if hydrophilic polymer solutes such as polyethylene glycol take part.…”
Section: Introductionmentioning
confidence: 99%